The Effects of Different Nickel–Ruthenium on SiO2 Catalyst Synthesis Methods toward Catalytic Activity of Methane Dry Reforming - Anatta Wahyu Budiman; Nisriina 'Abidah Qurrotul'aini; Nurul Latifah; Puan Hemas Dewani; Shafira Rachmadhani; Sofiana Mukti Wigati (Equilibrium Journal of Chemical Engineering, 2021)
The presence of greenhouse gases in the atmosphere has triggered global warming and climate change. An effective approach to overcome these issues is to convert greenhouse gases into syngas. In this study, Ni-Ru/SiO2 catalyst was used to catalyze the dry reforming process of methane (CH4) and carbon dioxide (CO2) into syngas. The catalyst was prepared using different synthesis protocols: sol gel-coprecipitation and impregnation methods. Characterization using Brunauer Emmett Teller analysis showed that the catalyst prepared using both methods exhibited comparable pore diameters and high surface areas. The X-ray diffractometer analysis also indicated the presence of different NiO, RuO2, and SiO2 phases. Furthermore, the activity of the catalyst was investigated using a fixed bed reactor. Based on the results, the optimum catalytic activity was obtained from the catalyst prepared via the sol gel-coprecipitation method, with an average CH4 and CO2 conversions of 37% and 50%, respectively. In addition, our catalyst also showed a 114% higher CH4 conversion with an enhanced H2/CO ratio compared to identical catalysts from other studies.